2015
DOI: 10.1097/wno.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Positive Apraclonidine Test in Horner Syndrome Caused by Thalamic Hemorrhage

Abstract: Reversal of anisocoria following instillation of apraclonidine 0.5% has been reported in Horner syndrome caused by lesions of the central and peripheral nervous system. The shortest documented latency between symptom onset and a positive apraclonidine test is 36 hours, occurring in a patient with a pontomedullary infarct. We present the case of a 69-year-old man with Horner syndrome due to thalamic hemorrhage in whom apraclonidine testing demonstrated reversal of anisocoria 4 days after symptom onset. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, previous studies reported that apraclonidine testing was positive within 1 week of carotid artery dissection [6] and 1.5 days of central causes such as thalamic hemorrhage [10], there has been no consensus how early apraclonidine will be positive in the setting of postoperative cases or more peripheral lesion. Therefore, a diagnostic tool that does not require pharmacological testing may be beneficial in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies reported that apraclonidine testing was positive within 1 week of carotid artery dissection [6] and 1.5 days of central causes such as thalamic hemorrhage [10], there has been no consensus how early apraclonidine will be positive in the setting of postoperative cases or more peripheral lesion. Therefore, a diagnostic tool that does not require pharmacological testing may be beneficial in clinical practice.…”
Section: Introductionmentioning
confidence: 99%